Conhecimento tático declarativo no futebol: dualidade intuição-deliberação na tomada de decisão - Ricardo Leão de Andrade (2013)
This study was aimed at investigating the effects of expertise level on the expression of Tactical Declarative Knowledge (TDK) and the "Take the First" (TTF) Heuristic in young football players, through a divergent thinking task performed under time and visual constraints. The sample was composed of 260 players from 8 teams of regional (4) and national (4) competitive level, in the age groups U-15 (4) and U-17 (4). In order to asses TDK, the test developed by Mangas (1999) and adapted by Giacomini (2007) was employed. In addition, this study innovated by incorporating two features to the test: participants were given the chance to generate their own answers, giving rise to the Tactical Declarative Knowledge Test - Option Generation Paradigm (TCTD-OGP); visual constraints (exposure or occlusion of the image after freezing the scene at the moment of decision making) and time constraints (12-s or 6-s interval for the option generation phase) were implemented. The results confirmed the regularity and robustness of the TTF heuristic, evidenced by its overall relative frequency of 69.81%. The following hypotheses of the study were confirmed: the quality of the option decreased as a consequence of its position in the sequence of options generated; the first options were generated and the final decisions were selected on the basis of the quality of the solutions; the probability of occurrence of the dynamic inconsistency (DI) increased when the number of options generated by the participants increased. It was also verified that the average quality of the final decision (FD) was superior to that of the first option (FO), suggesting that, when the ID occurred, the athletes were able to improve their choices throughout the option generation phase. Regarding the manifestation of TDK, it was demonstrated that players from higher competitive levels proposed not only a greater amount of options for the resolution of game situations, but also that these options presented greater convergence with the solutions proposed and validated by the experts in the original study. Taken together, the findings point in the direction of the interaction and interdependence of intuitive and deliberative processes for generating possibilities of action and choosing the preferred option. The implementation of visual constraints in the TCTD-OGP compromised both the quality of the FO and of the FD, with the effect on the latter presenting a greater magnitude. Different time-pressure conditions (12-s or 6-s for generating options) had an influence only on the average number of options generated. In this sense, the results suggest that: visual occlusion impacts negatively the ability of players to establish connexions between their mental representations of game situation and their knowledge of the game, in order to generate options and choose the best of them, indicating that working memory plays an important role in tactical decision-making; the 6-second interval was sufficient for reading game situation and generating options by the players, but it was a relatively long period for investigating the process of decision-making, especially in the scope of team sports.